A Randomized Controlled Trial of Moral Reasoning Training versus General Life Skills Training to Reduce Impulsivity and Non-Suicidal Self-Injury in Adolescents - Sharifi, Sajedeh; Doshmanfana, Saeed; Yousefvand, Fateme; Teimouri, Mahsa; Khalednejad, Mona (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to evaluate whether a manualized Moral Reasoning Training (MRT) reduces impulsivity and non suicidal self injury (NSSI) in adolescents more effectively than an active General Life Skills Training (LST) control, and to test whether changes in moral reasoning mediate intervention effects.Methods and Materials: In a single blind, parallel group randomized controlled trial, 240 adolescents (aged 13–17) reporting recent NSSI or elevated impulsivity were randomized to MRT (n = 120) or LST (n = 120). Both interventions comprised eight weekly 90 minute group sessions and were matched for duration and facilitator contact. Primary outcomes were monthly NSSI episode frequency (clinician interview) and trait impulsivity (self report Barratt Impulsiveness Scale); secondary outcomes included principled moral reasoning (DIT 2), behavioral inhibition (Go/No Go), emotion regulation (DERS), depressive symptoms, and global functioning. Assessments occurred at baseline, post treatment (8 weeks), and 3, 6, and 12 months. Analyses followed intent to treat principles using mixed effects models and longitudinal mediation with bootstrapped confidence intervals.Findings: Retention at 12 months was 84%. MRT produced significantly greater reductions in monthly NSSI episodes at post intervention compared with LST (adjusted incidence rate ratio = 0.62, 95% CI 0.50–0.77, p < .001) and larger decreases in trait impulsivity (between group Cohen’s d = 0.42 at post; maintained at 12 months). MRT participants showed larger gains in principled moral reasoning (mean DIT 2 increase ≈ +6.2 vs +1.8) and greater improvement on behavioral inhibition tasks. Longitudinal mediation indicated that DIT 2 change accounted for approximately 45–50% of MRT’s effect on impulsivity and NSSI. Interventions were feasible and safe; no trial related serious adverse events occurred.Conclusion: Targeted moral reasoning training yielded clinically meaningful and durable reductions in impulsivity and NSSI relative to an active life skills control, with mediation by enhanced principled moral reasoning and corroborating behavioral evidence. MRT represents a promising, mechanism based approach for school delivered prevention of adolescent self injury.